2007
DOI: 10.1007/s00423-007-0153-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategy for synchronous metastases of colorectal cancer: is hepatic resection after an observation interval appropriate?

Abstract: The outcome was similarly favorable in cases of synchronous hepatic metastasis and in cases of metachronous metastasis. Delaying resection allows accurate understanding of the number and location of hepatic metastases, and is beneficial in determining candidates for surgery and in selecting surgical procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Tumor diameter and number of metastases were tested for significance with the t test, and surgical procedure and recurrence in remnant liver were tested for significance with the chi-squared test After hepatic resection, recurrence was seen in the remnant liver in 44 (26.8%) cases, and the 3-and 5-year cumulative survival rates were 71.9% and 51.8%, respectively. The posthepatectomy outcome in cases of synchronous hepatic metastasis was similarly favorable with that in metachronous metastasis [1]. Our treatment outcomes were much better than those in reports of other authors [4][5][6][7][8].…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Tumor diameter and number of metastases were tested for significance with the t test, and surgical procedure and recurrence in remnant liver were tested for significance with the chi-squared test After hepatic resection, recurrence was seen in the remnant liver in 44 (26.8%) cases, and the 3-and 5-year cumulative survival rates were 71.9% and 51.8%, respectively. The posthepatectomy outcome in cases of synchronous hepatic metastasis was similarly favorable with that in metachronous metastasis [1]. Our treatment outcomes were much better than those in reports of other authors [4][5][6][7][8].…”
Section: Discussionsupporting
confidence: 62%
“…The basic policy at our hospital for colorectal cancer with synchronous hepatic metastasis has been to resect the primary colorectal cancer, followed if necessary by resection of the hepatic metastasis after an observation interval of 3 months. We have reported that the posthepatectomy outcome in our cases of synchronous hepatic metastasis was similarly favorable with that in metachronous metastasis [1]. In the present study, we investigated the changes in hepatic and extrahepatic metastatic foci during the observation interval and indicated the validity of observation interval for synchronous hepatic metastases.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…CRC patients with synchronous liver metastases are known to have a poorer prognosis than patients with metachronous liver metastases 7,8) . The potential occult liver metastasis is pointed out in patients with synchronous liver metastases and it was reported that new metastatic lesions may appear in these patients during three months after the resection of primary colonic tumor 9) . In the present case, a solitary liver metastasis was found preoperatively, and postoperative treatment with SOX plus BV was successfully performed.…”
Section: Discussionmentioning
confidence: 99%